Expansão de fronteiras e mudanças no uso do solo em Goiás - PRADO, Lícius de Albuquerque (2009)
The objective of this study is to identify and evaluate the relationship between the natural space and its use anthropic process and how it conditioned the expansion of Frontier in Goiás. Will be present a theoretical model that correlates the variable topography, fertility, and location with the land use spatialization in respect of classes of agriculture, pasture and native vegetation. The tests were conducted in the municipalities of Mineiros (16 º 50'00 "and 18 º 50'00" South Latitude and 52 º 10'00 "and 53 º 10'00" West Longitude) on the southwest of Goiás and Catalão (17 ° 27'24, 03 "and 18 ° 29'59, 35" South Latitude and 47 ° 15'48, 69 "and 48 ° 10'22, 36" W), southeastern state. It was used six scenes of the sensor of Landsat MSS (in digital format), obtained during the dry season and made up of four multispectral bands (bands 4, 5, 6 and 7). It was performed supervised classification by the classifier MAXVER and reproduced land use and land cover maps for 1975 (Mineiros) and 1979 (Catalão). Later maps were compared with the original data PROBIO for the year 2002. The results showed that the municipality of Mineiros in 1975 had 42.83% of its area on Oxisols, which concentrated 75.81% of the area of agriculture and 45.16% of the pasture area. In 2002, the Oxisols held 50.08% of the agriculture of the county and 40.03% of the pasture. This has become significant also in Ultisols and Neosols. In Catalão, Oxisols and Inceptisols occupy more than 85% of the total area of the municipality, and therefore, these soils are located most of the properties with agricultural activities. In turn, the slope factor has a major influence on agriculture of Mineiros and Catalão. The percentage of agricultural areas situated on slopes of up to 5° was approximately 95% for both periods analyzed in Mineiros and 89% (1975) and 94% (2002) in Catalão. When analyzing the location factor, both in Mineiros and in Catalão is evident the strong influence of the roads in agricultural areas of the municipalities. The kilometer closer of the roads is that the greatest number of agricultural areas. This percentage gradually decreases as it moves away from the influence of the roads. Given this context, it was verified that the areas that have a combination of natural factors studied are occupied first and stand out as being of high agricultural potential. Thus the agricultural areas are concentrated in areas of flatter topography, and soils are suitable and, above all, are close to major highways that cross the municipalities.